2022
DOI: 10.1155/2022/5387005
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Expression of Inflammatory Factors and T Cell Lymphocyte in Patients with Orthopedic Trauma after Infection and Risk Factors

Abstract: Since most orthopedic patients’ wounds are open in clinical practice, postoperative wound infection and other conditions are prone to occur, which pose varying degrees of threat to patients’ prognosis and life and health. In this paper, a retrospective study is conducted on orthopedic trauma patients in our hospital from January 2020 to January 2022, including 98 patients with postoperative infection and 98 patients without infection, to detect and compare the levels of inflammatory factors and the level of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%